A comparison study from a creative thinking perspective in different domains as art education and non-art education students - Ulger, Kani (Creativity Studies, 2023)
Creative thinking measurement for everyone in different domains is the most crucial critical subject. Therefore, the current discussion continues whether creativity in various fields different.This study aimed to measurement the students’ creative thinking scores in various domains disciplines to reveal differences. The main research question was as followed: Do whether students’creative thinking scores of students in art and non-art education differ significantly? The method was a causal-comparative research design. Participant students (N = 456, meanage = 16–21) were equivalent regarding some variations; as education disciplines and ages. While however, the art and non-art education students were the domain-specific was art education students, the and domaingeneral,was non-art education students respectively. The present study determined a significant difference between domain-specific and domain-general on creative thinking scores in favor of the non-art education students in the range of ages 16 to 21. The study concluded that alternative instruments with domain-specific content needed to measure individuals’ creative thinking in the domain-specific. This study suggested future research to conduct creativity measurement comparatively individuals in different age ranges and domains fields.